Aerobic Denitrification Microbial Community and Function in Zero-Discharge Recirculating Aquaculture System Using a Single Biofloc-Based Suspended Growth Reactor: Influence of the Carbon-to-Nitrogen Ratio - Deng, Min; Dai, Zhili; Senbati, Yeerken; Li, Lu; Song, Kang; He, Xugang (Frontiers in Microbiology, 2020)
In this study, the effect of aerobic denitrification on nitrogen removal was investigated using two zero-discharge biofloc-based recirculating aquaculture systems with representative carbon-to-nitrogen (C/N) ratios of 15 (CN15) and 20 (CN20). Aquaculture wastewater, residual feed, and fish feces were treated in an aerated suspended growth reactor (SGR, dissolved oxygen > 5.0 mg L−1). Low toxic NH3 (< 0.1 mg L−1) and NO2−-N (< 0.5 mg L−1) concentrations and high NO3−-N (83.3%) and NO2−-N (100%) removal efficiencies were achieved in the fish tank and SGR of CN20, respectively. The nitrogen mass balances indicated that the gaseous nitrogen loss accounted for 72%–75% of the nitrogen input. Illumina sequencing and quantitative polymerase chain reaction revealed that increasing the C/N ratio significantly increased the amount of aerobic denitrifying bacteria (Dechloromonas, Rhodobacter, Flavobacterium, and Zoogloea) and aerobic denitrifying functional genes (napA, nirK, and nosZ). Autotrophic Nitrosomonas was the dominant nitrifying bacteria in the CN15 system, and autotrophic (Nitrosomonas) and heterotrophic nitrifiers coexisted in the CN20 system. Moreover, the functional prediction analysis showed that the carbohydrate, energy, and amino acid metabolisms in the SGR of the latter increased. In conclusion, aerobic denitrification should widely exist in biofloc systems.